Viral mutation and substitution: units and levels. - Belshaw, R; Sanjuán, R; Pybus, O (2011)
Viruses evolve within a hierarchy of organisational levels, from cells to host species. We discuss how these nested population structures complicate the meaning and interpretation of two apparently simple evolutionary concepts: mutation rate and substitution rate. We discuss the units in which these fundamental processes should be measured, and explore why, even for the same virus, mutation and substitution can occur at very different tempos at different biological levels. In addition, we explore the ability of whole genome evolutionary analyses to distinguish between natural selection and other population genetic processes. A better understanding of the complexities underlying the molecular evolution of viruses in natural populations is needed before accurate predictions of viral evolution can be made.